Critical Assessment of Estimation Procedures for Floor Acceleration Demands in Steel Moment-Resisting Frames - González, Isaac; Silva, António; Macedo, Luís; Monteiro, Ricardo; Castro, José Miguel (Frontiers in Built Environment, 2019)
Performance-based earthquake engineering has increased the need for practical ways to assess the response of non-structural components (NSCs), which may be affected by deformation and/or acceleration demands of the superstructure. In the research study detailed in this paper, peak floor accelerations (PFAs) and floor response spectra (FRS) are computed using nonlinear response-history analysis (NTHA) for a comprehensive suite of 30 steel moment-resisting frame (MRF) archetypes, designed in accordance to Eurocode 8, considering different levels of nonlinear seismic demand. The mean trends observed were compared with the most recent approaches proposed in the literature for the prediction of acceleration demands. It was found that for PFAs, the available methods provide accurate predictions of the actual structural response under elastic and inelastic demands. However, the estimation procedures for the FRS yielded relevant differences in comparison to the observed elastic and inelastic responses, which points to the need for further development of such methods. It was also concluded that the existing PFA and FRS estimation methodologies present in several guidelines for seismic design and/or assessment do not provide reliable estimates of the acceleration demands imposed to buildings. This highlights the very important need for an improvement of these codified procedures for a more reliable prediction of seismic response.